Effect of Carnitine on Physico-Morphological Properties of Cryopreserved Hariana Bull Spermatozoa - Yadav, Brijesh Kumar; Gangwar, Kavisha; Agrawal, Jitendra Kumar; Sachan, Vikas; Yadav, Brijesh; Kumar, Anuj; Saxena, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The goal of current investigation was to ascertain the impact of carnitine as an additive in tris-egg yolk-based extender in Hariana bull semen chosen for cryopreservation. Progressive motility, viability, HOS response, and acrosomal integrity during thawing and equilibration were estimated. The post-thaw stage of seminal plasma enzymes was assessed, and the activity of the enzymes malondialdehyde (MDA), glutathione-S-transferase (GST), and superoxide dismutase (SOD) were quantified. Four Hariana bulls provided thirty-two ejaculates, which were divided into four aliquots. Aliquot was diluted in egg yolk tris glycerol (EYTG). Group I was treated with no carnitine; Group II received 2.5 mM of carnitine; Group III received 5 mM of carnitine; and Group IV received 10 mM of carnitine/100×106 spermatozoa. When 5 mM Carnitine was supplemented into semen, it significantly (p
Keywords: Bull semen; Carnitine; Cryopreservation; Hariana; Oxidative stress